2016
DOI: 10.1155/2016/7130653
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Stimulates Osteogenic Differentiation of Rat Bone Marrow Stromal Cells via Activation of the Notch Signaling Pathway

Abstract: Naringin is a major flavonoid found in grapefruit and is an active compound extracted from the Chinese herbal medicine Rhizoma Drynariae. Naringin is a potent stimulator of osteogenic differentiation and has potential application in preventing bone loss. However, the signaling pathway underlying its osteogenic effect remains unclear. We hypothesized that the osteogenic activity of naringin involves the Notch signaling pathway. Rat bone marrow stromal cells (BMSCs) were cultured in osteogenic medium containing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…Rhizoma Drynariae and its bioactive constituents were able to promote the osteoblastic proliferation, differentiation, and maturation (56,58,59,(62)(63)(64)(65)(66)(67)(68)(69)(70), inhibit osteoblastic apoptosis (71), suppress osteoclastogenesis (72)(73)(74), promote the apoptosis of osteoclasts (60), stimulate both cellular and humoral immunity (75), and inhibit cathepsins K processing (76,77).…”
Section: In Vitro Preclinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizoma Drynariae and its bioactive constituents were able to promote the osteoblastic proliferation, differentiation, and maturation (56,58,59,(62)(63)(64)(65)(66)(67)(68)(69)(70), inhibit osteoblastic apoptosis (71), suppress osteoclastogenesis (72)(73)(74), promote the apoptosis of osteoclasts (60), stimulate both cellular and humoral immunity (75), and inhibit cathepsins K processing (76,77).…”
Section: In Vitro Preclinical Datamentioning
confidence: 99%
“…Mechanisms involved in the osteogenesis and osteolysis effect of Rhizoma Drynariae and its components included: i) promote proliferation, differentiation, and maturation of rat calvarial osteoblasts (64) and UMR-106 osteoblastic cells (58,68) via ER pathway, ii) promote osteoblastogenesis from rat BMSCs via the Notch signaling pathway (70), iii) inhibit osteoclastogenesis of human amniotic fluid-derived stem cells (hAFSCs) via elevating OPG/RANKL ratio and induce the osteogenesis of hAFSCs via the BMP and Wnt/β-catenin pathways (72), and iv) promote the apoptosis of osteoclasts by regulating the mitochondrial apoptosis pathway using RAW 264.7 cells (60).…”
Section: In Vitro Preclinical Datamentioning
confidence: 99%
“…Naringin offers several advantages in comparison to synthetic pro‐osteogenic pharmaceutics or to recombinant BMP‐2. For instance, in comparison with Dex, Naringin is capable of repressing adipogenesis while solely promoting the osteogenic commitment of human bone marrow–derived mesenchymal stem cells (hBM‐MSCs) . Also, Dex systemic administration is characterized by a plethora of deleterious side effects, while Naringin is recognized to possess a wide range of antioxidant, anti‐inflammatory, anticancer, and antimicrobial activities .…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of 1–100 μg/mL was found to increase proliferation of human bone marrow stem cells (BMSCs), meanwhile a dose of 200 μg/mL caused rapid decrease in number of cells, suggesting a toxic effect of this or higher concentration (Zhang et al , ). However, Yu et al observed a suppressive effect on proliferation of rat BMSCs treated even with 100 μg/mL naringin (Yu et al , ).…”
Section: Plant‐derived Bioactive Compoundsmentioning
confidence: 99%
“…It also may be extracted from citrus fruits, such as grapefruit (Cao et al , ). Naringin was shown to increase the expression of osteoblastic markers both in rat and human BMSCs (Yu et al , ; Zhang et al , ). Moreover, naringin has been reported to prevent the decrease of β‐catenin and cyclin D1, the transcriptional regulators of Wnt signalling pathway, in hydrogen peroxide‐treated hADMSCs, thus protecting it against inhibition of osteogenic differentiation (Wang et al , ).…”
Section: Phytoestrogensmentioning
confidence: 99%